Human values in intercultural communication : CDA for Discourse of Proverbs in Yemen Times / Abduljalil Hazaea - Abduljalil, Hazaea (Universiti Teknologi MARA, Perak, 2017)
In intercultural communication, human values need to be investigated as neutral discourse; where local and global identities compete to legitimate such neutral discourse. Human values can be explicitly or implicitly manifested in the discourse of proverbs. Proverbs are ‘common sense’ assumptions that construct culturally-biased and durative values. Like newspaper headlines, proverbs are part of argumentative rhetoric whose semantic and pragmatic functions are not only to attract readers but also to convince them. As a subjournalistic genre in Yemen Times, the discourse of proverbs targeted worldwide audiences; it was produced by a non-local journalist and published in hardcopy and online between 2003 and 2010. This paper investigates human values in an intercultural text disseminated in global journalism; the discourse of proverbs of Yemen Times. The analytical tools of Critical Discourse Analysis (CDA) were employed to reveal the evident competing discourses associated with human values in the texts. The data analysis revealed that human values were associated with literary, philosophical, political and anonymous global discourses; these discourses were dominant in the texts. Local legitimating discourses were excluded; backgrounded local religious discourse and discourse of local passive agency were associated with human values. The exclusion of local agencies reflects hegemonic global power over human values in intercultural communication.